Contributors to Enhanced CO2 Electroreduction Activity and Stability in a Nanostructured Au Electrocatalyst - Kim, Haeri; Jeon, Hyo Sang; Jee, Michael Shincheon; Nursanto, Eduardus Budi; Singh, Jitendra Pal; Chae, Keunhwa; Hwang, Yun Jeong; Min, Byoung Koun (WILEY-V C H VERLAG GMBH, 2016)
The formation of a nanostructure is a popular strategy for catalyst applications because it can generate new surfaces that can significantly improve the catalytic activity and durability of the catalysts. However, the increase in the surface area resulting from nanostructuring does not fully explain the substantial improvement in the catalytic properties of the CO2 electroreduction reaction, and the underlying mechanisms have not yet been fully understood. Here, based on a combination of extended X-ray absorption fine structure analysis, X-ray photoelectron spectroscopy, and Kelvin probe force microscopy, we observed a contracted Au-Au bond length and low work function with the nanostructured Au surface that had enhanced catalytic activity for electrochemical CO2 reduction. The results may improve the understanding of the enhanced stability of the nanostructured Au electrode based on the resistance of cation adhesion during the CO2 reduction reaction.
Keywords: CARBON-DIOXIDE REDUCTION; ELECTROCHEMICAL REDUCTION; PARTICLE-SIZE; GOLD; SURFACE; REACTIVITY; ELECTRODES; OXIDATION; OXYGEN; CATALYSIS